The Influence Of Augmanted Virtual Reality Try-On On The Purchase Intention Of Cosmetics In Indonesia - Junia Ariani; Sudjaka, Jeremy Martin; Maydavania , Michelle Madeline; Saskia , Tresa Ivani (Universitas Muhammadiyah Pontianak, 2026)
This study investigates the influence of Augmented Reality Virtual Try-On (AR VTO) on cosmetic purchase intention in Indonesia, focusing on Hedonic Motivation, Pleasure, Arousal, and Dominance. Using a quantitative approach with multiple linear regression analysis on 105 respondents, the results show that Arousal and Dominance significantly affect purchase intention, while Hedonic Motivation and Pleasure do not. These findings imply that emotional stimulation and user control in AR experiences are key drivers of purchase behavior. The study provides practical insights for cosmetic brands to enhance AR features that improve consumer engagement and confidence in purchasing decisions.